Lipid fluidity at different regions in LDL and HDL of β-thalassemia/Hb E patients - Noppawan Phumala Morales (2018)
Atherosclerosis-related vascular complications in β-thalassemia/hemoglobin E (β-thal/Hb E) patients may result from iron induced oxidation of lipoproteins. To identify the specific site of oxidative damage, changes in lipid fluidity at different regions in LDL and HDL particle were investigated using two fluorescence probes and two ESR spin probes. The magnitude of increased lipid fluidity in thalassemic lipoproteins was dependent on the location of the probes. In hydrophobic region, the rotational correlation times for 16-doxyl stearic acid and DPH anisotropy were markedly changed in LDL and HDL of the patients. In the surface region, there was only a slight change in the order parameter (S) for 5-doxyl stearic acid and TMA-DPH anisotropy. Lipid fluidity at the core of LDL and HDL showed good correlation with oxidative stress markers, the ratio of CL/CO, and the level of α-tocopherol, suggesting that hydrophobic region of thalassemic lipoprotein was a target site for oxidative damage. © 2006 Elsevier Inc. All rights reserved.